Report of the Working Group on States' Resources for the Tenth Five Year Plan (2002-2007) Volume - 1 February 2002 - Planning Commission (Planning Commission, 2002)
In the context of projecting the size of States’ Aggregate Plan Resources for the Tenth Plan, the Working Group had to strike a balance between two seemingly conflicting requirements. One, which sought a real step up of Plan resources over Ninth Plan levels and two, which prevented the States' burden from becoming unsustainable. The apparent conflict if any was resolved by restricting the States' debt burden to current levels in relation to GSDP. Thereafter a step up over Ninth Plan resources was left to possible improvements in nondebt contribution to Plan resources, mainly the Balance from Current Revenues (BCR)
Government of India Planning Commission New Delhi
Government of India Planning Commission
Keywords: Constitution and Terms of Reference of the Working Group/Sub-Groups; Issues in Plan Financing; Projection of States’ Resources in the Tenth Plan 2002-07; Report of the Working Group; Working Group on States’ Resources; Sub- Group on Revenue and Expenditure; Net Borrowings NB